THE EFFECT OF SHIELDING GAS ON SURFACE DEFECTS AND MECHANICAL PROPERTIES OF MATERIALS AFTER THE GMAW WELDING - Catrawedarma, IGNB; Rosi, Azriel Alfito Dela; Wahid, M. Abdul; Pamuji, Dian Ridlo; Sari, Eli Novita; Fiveriati, Anggra (Otopro, 2024)
This research aims to analyze the strength and results of welded joints by testing non-destructive and destructive tests using CO2 and argon shielding gases. The type of welding used was gas metal arc welding with SS400 steel material. After welding, the material was tested using liquid penetrant, porosity, tensile, and bending tests. The results were that CO2 shielding gas tended to have a convex and wide shape, while the welding results from argon gas tended to have a small and flat shape. In both shielding gases, there were defects in undercuts, lack of fusion, and spatter after the liquid penetrant test. The porosity test results have circular spots and irregular lines with holes. The average tensile strength value obtained from argon shielding gas was 255.761 MPa, and CO2 shielding gas produced an average value of 219.671 MPa. The bending strength of the material with argon shielding gas obtained an average value of 729.00 MPa and CO2 gas shielding an average value of 611.99 MPa.